SSVSM-An SEO-SEM model to improve E-commerce product visibility - Ibrahim, Hassan; Rahmah, Mokhtar; Khan, Abdullah; Fauziah, Zainuddin (IJCESEN, 2025)
In the fast-paced world of e-commerce, especially on platforms like Amazon, standing out with your products is essential for attracting customers and boosting sales. Often, businesses rely on traditional Search Engine Optimization (SEO) and Search Engine Marketing (SEM) separately, which can lead to less-than-ideal outcomes. This paper introduces a new model called the Strategic SEO and SEM Visibility Model (SSVSM), which combines the best of both SEO and SEM to improve product visibility and rankings. The model uses a mix of on-page and off-page SEO techniques along with SEM strategies like pay-per-click (PPC), retargeting, and display ads, all while continuously optimizing in real-time. A case study was performed on Amazon.com, comparing products that were optimized using standard SEO/SEM methods (Group A) against those using the SSVSM hybrid model (Group B). The evaluation focused on key performance indicators such as ranking improvements, impression growth, conversion rates, and precision. The results showed that Group B outperformed Group A significantly, achieving a 4-page ranking boost, a 35% increase in impressions, a 20% conversion rate, and a precision rate that was four times higher than the control group. These findings confirm that the SSVSM model effectively targets the right users while maximizing both organic and paid traffic results. This research offers a practical and statistically backed framework for digital marketers and e-commerce businesses looking to enhance their visibility strategies in ever-changing online markets.